Evaluasi Capaian Pembangunan Daerah Berdasarkan Indikator Kinerja Utama Dan Indikator Kinerja Daerah - Irwan Safwadi; Saifuddin Saifuddin; Riki Musriandi; Usman Usman (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
This research is focused on knowing the achievement of the Main Performance Indicators (IKU) and Regional Performance Indicators (IKD) targets in the education sector in 2018, as well as analyzing the achievement of the 2019 targets listed in the 2017-2022 Nagan Raya RPJMK. By using secondary data, the data analysis process is carried out in a quantitative descriptive manner, comparing the achievements with the target indicators for the education sector listed in the RPJMK.  The evaluation results found that several key performance indicators had reached the target, such as the literacy rate and qualifications of D-IV and S1 teachers, although other indicators still require serious attention going forward. Regional performance indicators that achieve the target include APS, Continuing Rates from SMP/MTs to SMA/MA, Ratio of School Availability/Population Age Primary Education, Teacher/Student Ratio of Secondary Education Teacher/Student Ratio of Primary Education, and Qualified Teachers S1/D-IV. Other indicators include the expected number of years of schooling, GER, NER, the rate of continuing from SD/MI to SMP/MTs, the Ratio of School Availability/School Age Population of Secondary Education, and the Ratio of Teachers/Students Per Class Average of Primary Schools, should be a priority agenda. Future development to support the achievement of the regional vision and mission.